A multicentre, randomized, double‐masked, parallel group, vehicle‐controlled phase IIb study to evaluate the safety and efficacy of 1% and 3% topical minocycline gel in patients with papulopustular rosacea. (1st September 2020) - Webster, G.; Draelos, Z.D.; Graber, E.; Lee, M.S.; Dhawan, S.; Salman, M.; Magrath, G.N.
Summary: Background: Papulopustular rosacea is characterized by chronic facial erythema and inflammatory facial lesions. Minocycline has anti‐inflammatory properties which may be effective in the treatment of rosacea inflammatory lesions. Objectives: To assess the safety and efficacy of once‐daily topical minocycline gel 1% and 3% in patients with papulopustular rosacea. Methods: This was a prospective, 12‐week, double‐blinded study conducted at 26 sites in the United States; 270 patients with papulopustular rosacea and 12–40 inflammatory lesions were randomized to minocycline 1%, minocycline 3% or vehicle. The primary endpoint was the mean change in inflammatory lesions at week 12. Key secondary endpoints included success on an Investigator's Global Assessment (IGA). Results: Baseline mean lesion counts were 24·6, 25·1 and 24·3 in the minocycline 1%, minocycline 3% and vehicle groups, respectively; at week 12, the counts had decreased by 12·6, 13·1 and 7·9, respectively. Minocycline significantly decreased lesions, compared with the vehicle [ P = 0·01, 95% confidence interval (CI) 7·9 to 0·9, for minocycline 1%; P = 0·007, 95% CI 8·3 to 1·3, for minocycline 3%]. The proportion of patients achieving IGA success was 39% in the minocycline 1% arm [ P = 0·34, odds ratio (OR) 1·396 and OR 95% CI 0·71 to 2·75 vs. vehicle], 46% in the minocycline 3% arm ( P = 0·04, OR 2·03 and OR 95% CI 1·04 to 3·95 vs. vehicle) and 31% in the vehicle arm. Conclusions: Minocycline topical gel appears to be safe and tolerable at concentrations of 1% and 3%, and both concentrations significantly decreased inflammatory lesion counts, with a significantly larger proportion of patients achieving IGA success at week 12 in the minocycline 3% arm. These findings support further evaluation of minocycline gel for treating inflammatory lesions associated with papulopustular rosacea. Linked Comment: Hampton. Br J Dermatol 2020; 183 :412–413 .